HUBUNGAN ANTARA PARITAS DENGAN KEJADIAN PARTUS PREMATURUS IMMINENS DI RUMAH SAKIT UMUM SRIKANDI IBI JEMBER - Susilowati, Erwin; Rohmatin, Homsiatur; Hikmawati, Nova (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Imminent premature parturition (PPI) or the threat of premature birth is the presence of uterine contractions accompanied by changes in the cervix in the form of dilatation and efficiency before 37 weeks of gestation and can cause premature birth. The purpose of this study was to analyze the risk and the correlation between parity and imminent premature parturition at the Srikandi IBI General Hospital, Jember. This research used a quantitative approach with a cross sectional approach, the total sampling used was October 2022-March 2023. There were 43 cases. The results showed that most of the patients had premature births, 30 (69.8%) of the respondents. The risk of occurrence of parity in the primipara category or having 1 child is as many as 26 (60.5%) respondents. Based on statistical tests using chi square, the results obtained were p-value = 0.860 (α> 0.05) indicating that there was no relationship between parity and the incidence of parturition prematurus imminens at Srikandi IBI General Hospital, Jember. Suggestions for midwifery services are to provide special attention related to the handling of deliveries with complications that require immediate action so as to reduce maternal and infant mortality rates.